A Comprehensive Evaluation of Spine Kinematics, Kinetics, and Trunk Muscle Activities During Fatigue-Induced Repetitive Lifting. (September 2022) - Kazemi, Zeinab; Mazloumi, Adel; Arjmand, Navid; Keihani, Ahmadreza; Karimi, Zanyar; Ghasemi, Mohamad Sadegh; Kordi, Ramin
Objective: Spine kinematics, kinetics, and trunk muscle activities were evaluated during different stages of a fatigue-induced symmetric lifting task over time. Background: Due to neuromuscular adaptations, postural behaviors of workers during lifting tasks are affected by fatigue. Comprehensive aspects of these adaptations remain to be investigated. Method: Eighteen volunteers repeatedly lifted a box until perceived exhaustion. Body center of mass (CoM), trunk and box kinematics, and feet center of pressure (CoP) were estimated by a motion capture system and force-plate. Electromyographic (EMG) signals of trunk/abdominal muscles were assessed using linear and nonlinear approaches. The L5-S1 compressive force (Fc) was predicted via a biomechanical model. A two-way multivariate analysis of variance (MANOVA) was performed to examine the effects of five blocks of lifting cycle (C1 to C5) and lifting trial (T1 to T5), as independent variables, on kinematic, kinetic, and EMG-related measures. Results: Significant effects of lifting trial blocks were found for CoM and CoP shift in the anterior–posterior direction (respectively p < .001 and p = .014), trunk angle ( p = .004), vertical box displacement ( p < .001), and Fc ( p = .005). EMG parameters indicated muscular fatigue with the extent of changes being muscle-specific. Conclusion: Results emphasized variations in most kinematics/kinetics, and EMG-based indices, which further provided insight into the lifting behavior adaptations under dynamic fatiguing conditions. Application: Movement and muscle-related variables, to a large extent, determine the magnitude of spinal loading, which is associated with low back pain.